Cellular automata model based power network attack prediction technology - Lijuan YE; Yiting WANG; Licheng ZHU (Dianxin kexue)
The prediction range of the traditional power network attack range prediction technology was not wide enough, resulting in the poor effect of power network security improvement.For this reason, a power network attack prediction technology based on cellular automata model was proposed.A cellular automata model was built, regarding the cells in the cellular automata as power cells, a cell vitality value conversion rule was established and combined with the attack probability of attackers to predict the development and change of power cells.The power network attack was predicted according to the change trend of central power cells and neighboring power cells.The experimental result shows that, under the influence of time factors, the predicted attack node location of the proposed power network attack prediction technology based on cellular automata model is basically consistent with the original node, and the predicted load removal is always below 100 MW, the proposed technology is more effective.